Peculiarities of U(VI) sorption on composites containing hydrated titanium dioxide and potassium-cobalt hexacyanoferrate(II) - O. V. Perlova; Yu. S. Dzyazko; A. A. Malinovska; A. V. Palchik (Хімія, фізика та технологія поверхні)
As opposed to polymer sorbents, inorganic materials are stable against ionizing radiation. This gives a possibility to use them for the removal of radionuclides from water. As a rule, highly selective inorganic sorbents are obtained in a form of finely dispersive powder. This makes it difficult to use them in practice. Here the composites based on hydrated titanium dioxide containing K2Co[Fe(CN)6] have been developed. The modifier was inserted into partially (hydrogel) and fully (xerogel) formed oxide matrices. Modifying of hydrogel followed its transformation to xerogel provides the formation of potassium-cobalt hexacyanoferrate(II) nanoparticles (up to 10 nm), which are not washed out in aqueous media due to encapsulation in hydrated oxide. A number of the methods for sample characterization were used in this work: transmission electronic microscopy for vizualization of embedded nanoparticles, optical microscopy to measure granule size, FT-IR spectroscopy, X-ray fluorescence spectroscopy for chemical analysis of the samples, potentiometric titration to estimate ion exchange properties, and spectrophotometric analysis of the solution to determine U(VI) concentration. The features of U(VI) sorption from nitrate and sulfate solutions are considered: the effect of the sorbent dosage and solution composition was in a focus of attention. The influence of the modifier is the most pronounced at pH ? 4, when U(VI) is in a form of one-charged cations (UO2OH+): the removal degree of U(VI) is close to 100 %. This positive effect of the selective constituent is expressed in a presence of an excess of NO3–, SO42– and Na+ ions. The model of chemical reaction of pseudo second order has been applied to sorption. Both pristine sorbent and composite are most completely regenerated with a 0.1 M KOH solution - the regeneration degree is 92 and 96 % respectively. In this case, the half-exchange time is minimal and equal to » 23 min (initial hydrated titanium dioxide) and 47 min (composite). Desorption obeys the model of particle diffusion: the diffusion coefficients for ions being exchanged are (1.7–7.6)?10–13 m2s–1.